What Matters Most for Tertiary Education : A Framework Paper - Marmolejo, Francisco (World Bank, Washington, DC, 2017)
The main objective of this paper is to outline what policies matter most for an effective tertiary education (TE) system. It is crucial to ask not simply whether a system is working, but whether it is working to cope with current and expected demand in nations across the world. The paper presents the conceptual background and operational tools of the Systems Approach for Better Education Results (SABER)-TE domain. These tools are intended to be used by government education policy makers to assess policy areas of relevance to a country’s tertiary education system, benchmarking national policies against international best practices. The instruments are designed to be sensitive not only to the aggregation and benchmarking of best practices, but also to the disaggregation of the often-unintended effects of traditional tertiary education policies and practices. SABER-TE is intended to collect, synthesize, and disseminate comprehensive information on tertiary education to enable policy makers, the World Bank Group (WBG) staff, and development partners to learn how countries address similar policy challenges. The paper first provides a historical perspective on the World Bank’s involvement in tertiary education. Next, it discusses the importance that tertiary education has in today’s society and presents a brief review of the most significant issues and trends in tertiary education worldwide. In the second part of the document, the SABER-TE guiding principles are discussed, as well as the policy areas that the framework assesses. The document then describes instruments for data collection; a rubric for scoring, benchmarking, and analyzing the data; and methodological approaches for collecting and disseminating the findings of a SABER-TE assessment.